Internal marketing and the quality of service provided by the back-office to the front-office as key factor for customer satisfaction - Oliveira, Tânia (2012)
The increase of competitiveness amongst Mozambican financial institutions has led them to dedicate a considerable degree of attention to the quality of the services provided to the client. However, the focus of the Administration in defining strategic objectives and realizing bold commercial plans, often delegates the quality of internal services, between departments, namely the client-internal provider relations to the background. This article discusses an emerging subject in the organizational context, Internal Marketing and the adoption of this concept aims to improve the quality of the service offered by the Back-Office to the Front-Office of Millennium bim’s prime commercial network, by considering this relationship as a determining factor in the satisfaction of the external client. Hence, two questionnaires were conducted; one to 331 clients with accounts in the prime branches of the city of Maputo and the other to the 91 personnel at those branches, and the collected data was analyzed. Although the literature confirms that the satisfaction of the internal clients positively influences the satisfaction of the external clients, the results show an inverse relation between the satisfaction of the internal clients and the satisfaction of the external clients.